A primary estimate of global PCDD/F release based on the quantity and quality of national economic and social activities. (May 2016) - Wang, Bin; Fiedler, Heidelore; Huang, Jun; Deng, Shubo; Wang, Yujue; Yu, Gang
Abstract: The correlations between polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) releases and factors relevant to human social–economic activities (HSEAs) were analyzed. The multiple linear regression model was successfully developed to estimate the total global PCDD/F release. The PCDD/F releases significantly correlated with population, area, GDP and GNI, suggesting that "quantity" of HSEAs have significantly contributed to the PCDD/F releases. On another aspect, advanced technologies are usually adopted in developed countries/regions, and hence reduce the PCDD/F release. The significant correlation between PCDD/F release and CO2 emission implies the potential of simultaneous reduction of CO2 emission and PCDD/F release. The total global PCDD/F release from 196 countries/regions was estimated to be 100.4 kg-TEQ yr −1 . The estimated annual PCDD/F release per unit area ranged from 0.007 to 28 mg-TEQ km −2 . Asia is estimated to have the highest PCDD/F release of 47.1 kg-TEQ yr −1, almost half of the total world release. Oceania is estimated to have the smallest total release but the largest per-capita release. For the developed areas, such as Europe and North America, the PCDD/F release per unit GDP is lower, while for Africa, it is much higher. Highlights: Quantity and quality of economic and social activities determined PCDD/F releases. Human activity relevant factors were successfully used to estimate PCDD/F releases. The global PCDD/F release was firstly estimated to be about 100.4 kg TEQ yr −1 . Asia almost contributed half of the total global PCDD/F release. Oceania is estimated to have the least total but the largest per-capita release.